PELANGGARAN PRINSIP KERJASAMA (COOPERATIVE PRINCIPLE) DALAM PERCAKAPAN - Niswatin Nurul Hidayati (Al Hikmah: Jurnal Studi Keislaman, 2017)
In linguistics, a good communication can be measured by applying cooperative principle consisting of four maxims proposed by Grice (1989), but in the real communication, that principle is not always being obeyed and this phenomenon is called flouting maxim. This study reveals that flouting maxims are applied in a communication. There are 63 dialogues containing flouting maxims in the movie used by the author as the data source, and the most flouted is maxim of relevance. Flouting maxims lead to the implicit meanings of utterances, such as giving good impression, maintaining good relationship, giving proof/making sure, persuading the hearer, giving more information, applying politeness strategies, supporting hearer, making jokes, agreeing, and showing surprise. Then, most of intended meanings from the utterances being flouted are giving proof/making sure and applying politeness strategies.